Pengaruh Pola Pikir Kewirausahaan dan Ketahanan Psikologis terhadap Niat Menjadi Wirausaha Mahasiswa di Indonesia - Nabila Qinthara Putri; Dewi Kurniawati (LPPM Institut Pendidikan Nusantara Global, 2026)
Entrepreneurship is increasingly viewed as a strategic pillar of modern economic development due to its role in creating jobs, driving innovation, and strengthening national economic resilience. In Indonesia, the large demographic potential of the productive age group, particularly among students, makes entrepreneurship a relevant career alternative amidst technological disruption and market uncertainty. Rapid digital transformation, the expansion of the gig economy, and the growing demand for creative industries further highlight the importance of entrepreneurial competencies among young people. Universities, therefore, are expected not only to produce job seekers but also to nurture job creators who are capable of identifying opportunities and transforming ideas into sustainable ventures. However, the high level of entrepreneurial intention among students does not always translate into actual business creation. Various psychological factors, such as self-efficacy, risk tolerance, motivation, and resilience, play significant roles in shaping entrepreneurial behavior. Social support, access to capital, mentorship, and exposure to entrepreneurial role models also influence students’ readiness to start and sustain a business. Understanding these multidimensional determinants is essential to bridge the gap between intention and action. This study has contributions by enriching psychologically-based entrepreneurship studies, as well as practical implications for universities and policymakers in designing more adaptive, experiential, and sustainable entrepreneurship education programs that align with industry needs and national economic priorities.